(untitled) (Journal of Academic Research, 2023)
This study aimed to identify the concept of the museum and its importance, in addition to knowing the methods and methods of museum presentation used at the level of museums, and shedding light on the display methods within the Misurata Museum as a model, as the researcher relied on the use of the descriptive approach in the study, and on the interview and observation as main tools for collecting information. This study has been divided into three paragraphs, the first paragraph is the general framework of the study, the second paragraph is the concept of the museum, the importance and methods of museum display, and the third paragraph (the field study of the Misurata Museum), in addition to the most important findings and recommendations.